A Computational Unified Field Theorys Epilogue (CUFT): Possible Reversal of the Arrow of Time and Abolishment of Death (Global Journal of Science Frontier Research, 2018)
Introduction-21 st Century Physics is undergoing a major "Paradigmatic Shift" from its current "Material-Causal" Paradigm to the new 'A-Causal Computation' Paradigm associated with the 'Computational Unified Field Theory' (CUFT); As described previously [REF??] the need for such a 'Paradigmatic Shift' came about based on the existence of an apparent theoretical inconsistency between the two primary pillars of Physics, namely: Relativity Theory (RT) and Quantum Mechanics (QM) as well as a series of unresolved 'Physical Conundrums', e.g., including: "dark-matter" and "dark-energy" (which are purely hypothetical concepts referring to up to 85% of all of the mass and energy in the universe which cannot be observed empirically!?)